2014
DOI: 10.1105/tpc.114.129809
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Metabolites Enhance the Light Sensitivity of Arabidopsis Cryptochrome through Alternate Electron Transfer Pathways    

Abstract: Cryptochromes are blue light receptors with multiple signaling roles in plants and animals. Plant cryptochrome (cry1 and cry2) biological activity has been linked to flavin photoreduction via an electron transport chain comprising three evolutionarily conserved tryptophan residues known as the Trp triad. Recently, it has been reported that cry2 Trp triad mutants, which fail to undergo photoreduction in vitro, nonetheless show biological activity in vivo, raising the possibility of alternate signaling pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
101
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(114 citation statements)
references
References 52 publications
(102 reference statements)
8
101
3
2
Order By: Relevance
“…If the in vivo activity of Trp-triad mutants was caused by ATP-enhanced photoreduction, ATP would be expected to rescue light-dependent flavin reduction of the Trp-triad mutants that possess lightdependent physiological activities in vivo and to exert lightindependent enhancement of flavin reduction of the Trp-triad mutants that exhibit light-independent or constitutive activities in vivo. In contrast to both expectations, it had been reported previously that ATP enhanced light-dependent flavin reduction or photoreduction of the W374A mutant of CRY2 that is constitutively active in vivo (22,23) but failed to enhance photoreduction of the W397F mutant of CRY2 that showed light-dependent activities in plants (22,23). Similarly, ATP failed to enhance photoreduction of the W324A and W400F mutants of CRY1 ( Fig.…”
Section: Lack Of Correlation Between Atp-enhanced Photoreduction and Trpmentioning
confidence: 56%
See 1 more Smart Citation
“…If the in vivo activity of Trp-triad mutants was caused by ATP-enhanced photoreduction, ATP would be expected to rescue light-dependent flavin reduction of the Trp-triad mutants that possess lightdependent physiological activities in vivo and to exert lightindependent enhancement of flavin reduction of the Trp-triad mutants that exhibit light-independent or constitutive activities in vivo. In contrast to both expectations, it had been reported previously that ATP enhanced light-dependent flavin reduction or photoreduction of the W374A mutant of CRY2 that is constitutively active in vivo (22,23) but failed to enhance photoreduction of the W397F mutant of CRY2 that showed light-dependent activities in plants (22,23). Similarly, ATP failed to enhance photoreduction of the W324A and W400F mutants of CRY1 ( Fig.…”
Section: Lack Of Correlation Between Atp-enhanced Photoreduction and Trpmentioning
confidence: 56%
“…For example, Trp triad-dependent photoreduction is not required for the in vivo DNA-repairing activity of Escherichia coli photolyase (16)(17)(18), the photobiochemical and magnetosensing activities of Drosophila cryptochrome (10,13,(19)(20)(21), or the photobiochemical and photophysiological activities of Arabidopsis CRY2 (22). It was proposed recently that ATP or other metabolites may enhance the rapid photoreduction of CRY2 to "rescue" its defects in photoreduction and physiological activities in vivo (23). However, because Trp-triad mutations were reported to inactivate CRY1 (15) but not CRY2 in vivo (22), this interpretation raises the intriguing possibility that Arabidopsis CRY1 might possess a photoexcitation mechanism distinct from both the closely related Arabidopsis CRY2 and the remotely related E. coli photolyase and Drosophila cryptochrome.…”
mentioning
confidence: 99%
“…The ability to rescue photoreduction efficiency in a cellular system led to a hypothesis that cellular metabolites, such as ATP and NADH, may contribute to photoreduction in CRY proteins. Indeed supplementation of recombinant CRYs with ATP rescued photoreduction deficiencies of Trp triad mutants (4). These studies seemed to reconcile key elements of CRY photochemistry.…”
Section: Cry Photochemistrymentioning
confidence: 84%
“…Thus, researchers proposed that CRY proteins function independently of an antennae pigment and use oxidized FAD as the ground state. In addition, in vitro studies of CRY photochemistry indicated that photoreduction of oxidized FAD to either the neutral (FADH) or anionic (FAD-) semiquinone required the presence of the Trp triad and external electron donors (4,9). These studies led to a proposed mechanism for CRY activation, whereby, blue light excitation of an oxidized FAD ground state induced electron transfer through the Trp triad to generate a semiquinone signaling state (Fig.…”
Section: Cry Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation